Kegiatan Pengabdian Masyarakat Dengan Deteksi Dini dan Edukasi Kesehatan Kulit Melalui Pemeriksaan Kadar Minyak, Air, dan Hidrasi Kulit Pada Masyarakat di Krendang - Linda Yulianti W; Alexander Halim Santoso; Agustina Agustina; Angelica Devi Ratana (Institut Nalanda, 2025)
The levels of hydration, oil, and air in the skin are important aspects referring to the air content in cells and play a role in skin moisture so that it looks smooth and elastic. Low levels of hydration, oil, and air in the skin can damage the skin barrier which functions as a physical permeability barrier that is useful for protecting the body from the external environment and low levels of hydration are also indicators of systemic disorders. This activity was carried out in Krendang, a densely populated urban area in Jakarta, with the aim of screening for dry skin by examining the levels of air, oil, and skin hydration. This activity was attended by 131 adult participants. The Plan-Do-Check-Act (PDCA) method was applied, where the levels of air, oil, and skin hydration were measured, and educational materials were provided regarding dry skin and its risk factors. In this activity, the average oil levels in the right and left hands were 26.9% and 27% respectively, the water levels in the right and left hands were 54.25% and 54.69% respectively. Through this activity, participants are expected to increase awareness of the importance of optimal skin hydration status.